Expression of various polarization effects by using Spirulina-templated metal μcoils at the terahertz frequency region. (13th February 2019) - Notake, Takashi; Kamata, Kaori; Iyoda, Tomokazu; Otani, Chiko; Minamide, Hiroaki
Abstract: Spirulina-templated metal μ coils (STM μ C) are interesting materials for a wide range of terahertz (THz) applications due to their distinctive interactions with THz-light. We measured inclusive Mueller matrices of randomly distributed and one-dimensional (1D) STM μ C-embedded paraffin sheets using Stokes polarimetry at 1.6 THz, where strong optical activity has already been reported. We demonstrated that the one-dimensional STM μ C paraffin sheet can simultaneously express five polarization effects including linear-birefringence, linear-dichroism, circular-birefringence, circular-dichroism, and depolarization. Hence, STM μ C can potentially be utilized for the control of various polarization phenomena of THz-light.